Combatting Fibrosis: Exosome‐Based Therapies in the Regression of Liver Fibrosis - Chen, Li (Hepatol Commun, 2018)
Hepatic fibrosis results from chronic injury and inflammation in the liver and leads to cirrhosis, liver failure, and portal hypertension. Understanding the molecular mechanisms underlying hepatic fibrosis has advanced the prospect of developing therapies for regression of the disease. Resolution of fibrosis requires a reduction of proinflammatory and fibrogenic cytokines, a decrease in extracellular matrix (ECM) protein production, an increase in collagenase activity, and finally, a disappearance of activated myofibroblasts. Exosomes are nanovesicles of endocytic origin secreted by most cell types. They epigenetically reprogram and alter the phenotype of their recipient cells and hold great promise for the reversal of fibrosis. Recent studies have shown that exosomes function as conduits for intercellular transfer and contain all the necessary components to induce resolution of fibrosis, including the ability to (1) inhibit macrophage activation and cytokine secretion, (2) remodel ECM production and decrease fibrous scars, and (3) inactivate hepatic stellate cells, a major myofibroblast population. Here, we discuss the research involving the regression of hepatic fibrosis. We focus on the newly discovered roles of exosomes during fibrogenesis and as a therapy for fibrosis reversal. We also emphasize the novel discoveries of exosome‐based antifibrotic treatments in vitro and in vivo.